The effects of different repolishing procedures on the color change of bulk-fill resin composites - Muhammet Fidan (European Oral Research)
Purpose: The purpose of the study was to investigate the impact of repolishing procedures on the color change of bulk-fill resin composites after being exposed to coffee. Materials and methods: Four bulk-fill resin composites (Filtek One bulk‑fill, Tetric EvoCeram bulk-fill, Admira Fusion x-tra bulk-fill, Grandio SO x-tra bulk-fill) were tested. Sixty samples were prepared with each resin composite and were randomly divided into two groups: first one received the one-step polishing system (Optragloss) and the other group received the two-step polishing system (Nova Twist) (n=30). After being kept in coffee for 12 days, the samples were divided into three subgroups according to repolishing: one-step repolishing group, two-step repolishing group, and non-repolishing group (n=10 for each). Color measurements of the resin composite samples were determined with a spectrophotometer. The difference in color change was calculated using the CIEDE 2000 color formula. The data were analyzed using three-way ANOVA and Tukey test. Results: Among composite materials, Filtek One bulk-fill (1.84 ± 0.98) less color change was observed compared to others (p<0.001). In terms of polishing systems, Optragloss (2.96 ± 1.51) showed significantly greater color change than Nova Twist (2.21 ± 1.07) (p<0.001). The non-repolishing group (3.78 ± 1.25) presented significantly greater color change than the Nova Twist sytem (1.49 ± 0.61) and Optragloss system (2.50 ± 1.01) (p<0.001). Conclusion: The repolishing process reduced discoloration. A two-step repolishing system results in less color change compared to a one-step repolishing application. In polishingsystems containing diamond particles, increasing the number of steps can contribute to color stability.